Site Selection For Recreational Sports In Surabaya - Ilmi Lintang Cahyani; Farida Murti; Benny Bintarjo Dwinugroho Hersanyo (Kirana Publisher (KNPub), 2026)
Surabaya, as one of Indonesia’s largest urban centers, has strong potential for developing recreational sports due to its growing infrastructure and rising public awareness of healthy lifestyles. However, rapid urbanization also brings challenges, particularly changes in modern lifestyles that can negatively impact public health. To address this, recreational sports facilities must emphasize accessibility and equitable distribution so all communities can benefit. These facilities should accommodate diverse fitness activities while also serving as spaces for social interaction, supporting productivity and improving overall quality of life. This study aims to identify the most suitable site for designing recreational sports facilities for productive communities in Surabaya. The methodology involves analyzing potential locations based on specific site selection criteria. The evaluation follows standards proposed by Chou, which include physical and environmental conditions, accessibility and mobility, as well as surrounding factors that support operational effectiveness.